2018
DOI: 10.17338/trainology.7.1_10
|View full text |Cite
|
Sign up to set email alerts
|

Periodization for optimizing strength and hypertrophy; the forgotten variables

Abstract: Objectives: A growing area of discourse within sports medicine and resistance training is that of periodization. This has been represented as variation in load and subsequently repetitions as well as volume, with a view to maximize strength and hypertrophy adaptations. A number of recent review articles have attempted to draw overarching conclusions from the present body of literature in an effort to provide definitive guidelines. However, there are numerous variables within resistance training that are often … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Furthermore, variation can be accomplished by performing exercises with different joint angles (inclined vs. declined), grips (e.g., pronated vs. supinated), stance/grip widths (wide vs. narrow), and initial joint positions (stretched vs. shortened) (35). However, despite the common use of exercise variation as a strategy to enhance RT responses (16,21,22,47), the topic remains largely underresearched (19), making it difficult to draw conclusions as to its true effects on RT-induced muscular adaptations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, variation can be accomplished by performing exercises with different joint angles (inclined vs. declined), grips (e.g., pronated vs. supinated), stance/grip widths (wide vs. narrow), and initial joint positions (stretched vs. shortened) (35). However, despite the common use of exercise variation as a strategy to enhance RT responses (16,21,22,47), the topic remains largely underresearched (19), making it difficult to draw conclusions as to its true effects on RT-induced muscular adaptations.…”
Section: Introductionmentioning
confidence: 99%
“…Progressive overload is characterized by a gradual increase in stress imposed on the body, whereas variation refers to the systematic change of 1 or more variables (e.g., intensity, volume, exercise) throughout an RT program (1). Although the effects of the systematic changes in intensity and volume have been the most frequently investigated variables (1,18), variation also can be achieved by manipulating other RT components, such as exercise selection (1,19). In this regard, performing different exercises (i.e., exercise variation) has been proposed as a strategy to target multiple regions within a muscle group (i.e., different muscular heads) or even within a single muscle and thus potentially optimize muscle growth.…”
Section: Introductionmentioning
confidence: 99%
“…Some might consider the emergence of a plateau a result of unvaried stimuli in the standardised protocol employed, or that over time greater volumes of training are required to ensure continued adaptation. However, the hypothesis that variation in the specific variables that comprise a resistance training bout are required for continued strength adaptation in the long-term lacks a clear physiological rationale and empirical support (Fisher et al, 2018;Buckner et al, 2020). Meta-analyses on the effects of volume upon strength also suggest only trivially greater effects with moderate to higher volumes over the short term; further, they highlight that there is little data to enable identification of interaction effects with training experience (Ralston et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…One way to vary within the RT program is to perform different exercises for the same muscle group. However, this strategy is still overlooked, and the data available in the current literature are inconclusive (11). For example, Fonseca et al (13) pointed out an advantage in muscle strength gains when exercise variation was adopted, compared with a fixed exercise routine; however, Rauch et al (25) and Baz-Valle et al (4) showed no difference between the 2 routines.…”
Section: Introductionmentioning
confidence: 99%